1995
DOI: 10.1093/bja/74.4.458
|View full text |Cite
|
Sign up to set email alerts
|

Extradural ropivacaine and bupivacaine in hip surgery

Abstract: We studied 126 patients undergoing elective hip surgery; they received 20 ml of 0.5%, 0.75%, 1.0% ropivacaine or 0.5% bupivacaine extradurally in a double-blind design. Sensory block (pinprick), motor block (modified Bromage scale), quality of analgesia and neuromuscular block were assessed intermittently. Heart rate and arterial pressure were measured at regular intervals. A total of 115 patients were evaluated for efficacy. Onset of analgesia, onset of motor block and maximum cephalad spread (T4) did not dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0
8

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 3 publications
(2 reference statements)
6
17
0
8
Order By: Relevance
“…Deve-se salientar que a bradicardia pode representar efeito colateral importante em animais debilitados, apesar da ausência de hipotensão neste experimento. A lidocaína, especialmente, quando associada à adrenalina, apresenta lenta absorção sistêmica, determinando boa margem de segurança para o sistema cardiovascular, bem como a ropivacaína (WOLFF et al, 1995 adversos decorrentes do uso de ropivacaína (MARKHAM & FAULDS, 1996;PITHER et al, 2003). Embora haja relatos de que a ação (α2-adrenoceptora agonista da xilazina possa causar bradipnéia (KELAWALA et al, 1996), neste estudo, todos os parâmetros respiratórios apresentaram-se estáveis em todos os grupos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Deve-se salientar que a bradicardia pode representar efeito colateral importante em animais debilitados, apesar da ausência de hipotensão neste experimento. A lidocaína, especialmente, quando associada à adrenalina, apresenta lenta absorção sistêmica, determinando boa margem de segurança para o sistema cardiovascular, bem como a ropivacaína (WOLFF et al, 1995 adversos decorrentes do uso de ropivacaína (MARKHAM & FAULDS, 1996;PITHER et al, 2003). Embora haja relatos de que a ação (α2-adrenoceptora agonista da xilazina possa causar bradipnéia (KELAWALA et al, 1996), neste estudo, todos os parâmetros respiratórios apresentaram-se estáveis em todos os grupos.…”
Section: Discussionunclassified
“…Adicionalmente, a lidocaína é um fármaco de curta ação, sendo limitada em cirurgias prolongadas, havendo necessidade da associação com fármacos de longa duração (CRUZ et al, 1997;ISHIY et al, 2002). A ropivacaína, agente de longa duração e homóloga à bupivacaína, promove bloqueio sensitivo de duração igual ou discretamente inferior, com período de bloqueio motor e toxicidade nervosa e cardíaca menores que os daquele fármaco (WOLFF et al, 1995;FELDMAN et al, 1996).…”
Section: Introductionunclassified
“…In Bupivacaine group the mean duration was 391.1± 15.1 minutes, indicating that there was no difference in the duration of sensory analgesia among the two groups. In studies conducted by Brockway M S et al 5 , Finucane B T et al 13 Katz et al 14 Wolff A.P et al 15 and Brown DL. 16 et al it was found that there was no significant difference in duration of sensory analgesia when comparing Ropivacaine with Bupivacaine.…”
Section: Duration Of Sensoryanalgesiamentioning
confidence: 98%
“…Wolff A.P et al 15 found no difference in onset of sensory or motor block when comparing 0.5%, 0.75%, 1.0% Ropivacaine or 0.5% Bupivacaine administered extradurally in patients undergoing elective hip surgery.…”
Section: Onset Of Sensory and Motor Blockadementioning
confidence: 99%
See 1 more Smart Citation